2008
DOI: 10.1111/j.1365-2516.2008.01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemate® P/Humate‐P® for the treatment of von Willebrand disease: considerations for use and clinical experience

Abstract: von Willebrand disease (VWD) is a heterogeneous bleeding disorder with symptoms in affected patients ranging from mild effects to potentially devastating haemorrhagic events. Desmopressin (DDAVP) and von Willebrand factor/factor VIII (VWF/FVIII) concentrates are the principal treatments. Haemate P/Humate-P is an intermediate-purity VWF/FVIII concentrate with extensive clinical experience in VWD. This concentrate has been shown to correct haemostatic defects of VWD, with efficacy ratings of good/excellent in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…Therefore, many guidelines recommending PCC administration lack recommendations regarding the dosing regimen [9, 10, 18, 19]. In particular, the recommendations do not specify whether to use non-activated PCC preparations or, on the contrary, activated PCC preparations, known as anti-inhibitor coagulant complex or FEIBA (factor VIII inhibitor bypassing activity; available as FEIBA VH or Autoplex T) [22]. A recent trial concluded that an "individualized" dosage regimen of PCC based on target-INR, initial-INR and patient body weight is significantly more effective in reaching target INR than a fixed dose [23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many guidelines recommending PCC administration lack recommendations regarding the dosing regimen [9, 10, 18, 19]. In particular, the recommendations do not specify whether to use non-activated PCC preparations or, on the contrary, activated PCC preparations, known as anti-inhibitor coagulant complex or FEIBA (factor VIII inhibitor bypassing activity; available as FEIBA VH or Autoplex T) [22]. A recent trial concluded that an "individualized" dosage regimen of PCC based on target-INR, initial-INR and patient body weight is significantly more effective in reaching target INR than a fixed dose [23].…”
Section: Introductionmentioning
confidence: 99%
“…These agents have a long history of use with demonstrated efficacy with minimal side effects. 5 By having a greater awareness and comfort with vWD and how it is managed, the perianesthesia nurse can help to optimize surgical outcomes and avoid complications after ambulatory surgery.…”
Section: Discussionmentioning
confidence: 99%
“…10 Humate-P contains vWF as well as albumin and fibrinogen, which add to its efficacy in optimizing coagulation. 5 These agents are generally well tolerated, but if elevation of heart rate occurs, the infusion of the product should be slowed to optimize patient comfort. 5 Rarely a patient may show signs of an allergic hypersensitivity to the product, exhibiting symptoms such as pruritis, wheezing, hypotension, and chest tightness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Humate-P is a human plasma-derived vWF/FVIII concentrate with an extensive, three-decade track record of no thrombosis and no cases of viral transmission [12, 13]. It is recommended for surgical prophylaxis and spontaneous bleeding treatment in all types of vWD and in vWD cases that are refractory to desmopressin.…”
Section: Discussionmentioning
confidence: 99%